AB0382 A RITUXIMAB AND BELIMUMAB COMBINATION THERAPY IN SLE PATIENTS. (2nd June 2020) - Mesnyankina, A.; Solovyev, S.; Aseeva, E.; Nikishina, N.
Abstract : Background: Various mechanisms of action of RTM and BLM, in particular their interaction with defined subpopulations of B cells, can contribute to more effective suppression of autoreactive B cells and achieve a therapeutic effect. Objectives: To assess the efficacy of a rituximab and belimumab combination therapy in pts with active SLE. Methods: The study included 10 SLE pts (1М/9F) with high (SLEDAI2K≥10 – 8pts.) and moderate (SLEDAI2K<10- 2pts.) disease activity; out of them 2 patients had lupus nephritis, 2- vasculitis. 1 pts both (nephritis and vasculitis), and remaining 5 had predominantly mucocutaneous and articular manifestations of SLE. The dose of oral GCs at baseline did not exceed 20 mg/day in 9 pts, two pts were treated with prednisone 5 mg/day and only 1 received 60 mg. Rituximab (RTM) was administered at 500-2000 mg, with subsequent adding of Belimumab (BLM) 1-6 months later at a standard dosing regimen 10 mg/kg once a month. СD19+ В- lymphocytes counts were obtained before initiation RTM (0), and subsequently after 3 (N=10), 6 (N=10), 9 (N=7), and 12month (N=7). Depletion of CD19+ В- lymphocytes after RTM was assessed as the decrease of В-cell counts < 0, 01 10*9/l, where 0 10*9/l was categorized as complete depletion, from 0, 001 to 0, 01 10*9/l – partial depletion, and >0, 011 10*9/l – absence of depletion. The comparison group included 20 pts receiving a sing=ъ500-2000mg dose of RTM with high (SLEDAI2K≥10 – 16pts.) and moderate (SLEDAI2K<10- 4pts.) disease activity (SLEDAI Me 14[10;16]) Results: 6 pts demonstrated the decrease in clinical and laboratory SLE activity, starting from 3mo of follow-up, and by the 6th month the decrease in the activity of the disease was observed in 9 patients (SLEDAI-2K 0 mo–Me 12[10;16], 3mo-Me 8[6;10], 6mo–Me 4[2;6], 9mo–Me 6[4;10], 12mo–Me 2[2;6]) with RTM + BLM combination therapy. The oral GCs dose was reduced to 6, 9 [5;10]mg/day by 6mo. One patient managed to completely eliminate glucocorticoids; he continued to receive cytostatic therapy (mycophenolate mofetil). None of the patient required prednisone dose escalation during follow-up. There were no cases of severe infection. The damage index did not increase by 6 and12mo. The combination therapy reduced the absolute counts of CD19+. В-cells. RTM therapy resulted in complete depletion in 3 pts, in partial depletion - in 4. Addition of BLM resulted in slowing down of CD19+ В-cell repopulation (Fig.1) (0mo–Me 0, 11x10 9 /l[0, 08;0, 5], 12mo -Me 0, 01x10 9 /l[0, 01; 0, 03]) vs pts receiving RTM monotherapy (0mo–Me 0, 1x10 9 /l[0, 08;0, 2], 12mo -Me 0, 03x10 9 /l[0, 008; 0, 08]). RTM and BLM combination failure, as well as failure of standard GCS and cytostatic based therapy, was documented in one patient with cutaneous, articular and hematological SLE. Conclusion: Combination therapy allows to gain control over disease activity in short time, due to the effect of RTM, while added BLM provides further prolongation of the effect achieved, minimizing the risk of exacerbation. This combination may be used as a method of choice in pts with severe SLE involving vital organs, and in persistent cutaneous-articular disease and high immunological activity. In these patients there were no signs of infection. Disclosure of Interests: None declared